Emotional Competence, Entrepreneurial Self-Efficacy, and Entrepreneurial Intention: A Study Based on China College Students’ Social Entrepreneurship Project - Chien-Chi, Chu; Sun, Bin; Yang, Huanlian; Zheng, Muqiang; Li, Beibei (Frontiers in Psychology, 2020)
Entrepreneurship education has a lot of research on influencing factors of entrepreneurial intention, but rarely studies the influence mechanism of emotional competences on entrepreneurial intention from the perspective of social entrepreneurship. This article takes college students' social entrepreneurs as research objects, drawing on Krueger’s model, theory of planned behavior, social cognitive theory , and triadic reciprocal determinism theory, this paper constructs a conceptual model with emotional ability, entrepreneurial self-efficacy, and entrepreneurial intention, to further study their relationship. The 312 students from China enact us engaged in early entrepreneurship practice conducted a questionnaire survey and used the empirical test of the structural equation model to analyze the relationship between college students’ emotional competences, entrepreneurial self-efficacy, and entrepreneurial intention. The result show: First, social-emotional competence had a positive effect on entrepreneurial intention, and the positive effect of personal affective competence on entrepreneurial intention was not supported or only partially supported. Second, all the dimensions of entrepreneurial self-efficacy were significantly and positively correlated with entrepreneurial intention. Third, emotional competence has a significant positive impact on entrepreneurial self-efficacy. Fourth, entrepreneurial self-efficacy mediated the relationship between emotional competence and entrepreneurial intention.